Health Literacy Competencies for European Health Care Personnel - Karuranga, Suvi (Health Lit Res Pract, 2017)
BACKGROUND: Health literacy as a concept is gaining importance in European countries, although it is still not adequately addressed among health personnel. Health literacy supports the self-management of patients in maintaining and improving health, which could decrease the burden on health systems in Europe. However, health professionals lack adequate knowledge about health literacy and the skills to promote health literacy among their patients. OBJECTIVE: The Health Literacy Practices and Educational Competencies for Health Professionals (a health literacy training curriculum for health professionals) was recently developed in the United States, and the study presented here aimed to refine that assessment for health personnel in European settings. METHODS: The modified Delphi method was used and data collected online via electronic communication to achieve consensus among an expert panel. The participants were a group of 20 health literacy and health care experts from 10 professional fields representing 13 European countries. The participants rated health literacy competencies on a four-point Likert scale and provided written feedback and recommendations. If a predetermined threshold of 70% or more of the participants agreed on the competency, the consensus was defined (similar to the criteria in the Health Literacy Practices and Educational Competencies for Health Professionals intervention). KEY RESULTS: After three rounds of ratings and modifications, consensus agreement was reached on 56 health literacy competencies (20 knowledge items, 25 skills items, 11 attitude items) and 38 practices. Eight items were removed from the original list and eight new items were added to the final list. CONCLUSIONS: This study is the first known attempt to develop a measurable list of health literacy competencies for health personnel in Europe. Further work is needed to develop educational curricula, standard national and regional guidelines, and questionnaires for the process of implementation to maximize health literacy responsiveness in health care organizations. [Health Literacy Research and Practice. 2017;1(4):e247–e256.] PLAIN LANGUAGE SUMMARY: The Health Literacy Practices and Educational Competencies for Health Professionals was recently developed in the United States. This study aimed to refine that assessment for health care professionals in Europe. The modified Delphi method was used and data collected online via electronic communication, and in the end, 56 health literacy competencies were included.